163 Lox-1-specific affimers block oxldl accumulation in vitro. (5th June 2017) - De Siqueira, Jonathan; Abdul Zani, Izma; Russell, David; Wheatcroft, Stephen; Tomlinson, Darren; Homer-Vanniasinkam, Shervanthi; Ponnambalam, Sreenivasan
Abstract : Introduction: Lectin-like oxidised low density lipoprotein receptor 1 (LOX-1, SREC-1, OLR1) is a class E scavenger which binds oxidised low density lipoproteins (oxLDL). It is expressed on endothelial cells, macrophages and smooth muscle cells, where it has a major role in sensing oxLDL, in the triggering of cellular dysfunction and in contribution to atherosclerosis. LOX-1 is thus an important target for the prevention and/or treatment of atherosclerosis. Affimers are synthetic protein scaffolds containing two hypervariable amino acid loops which enable recognition of a wide range of molecules. We aimed to investigate whether affimers specific for LOX-1 could be used to target oxLDL recognition and uptake using an in vitro cellular model. Methods: Human embryonic kidney (HEK293T) and porcine aortic endothelial cells (PAEC) with tetracycline-inducible protein expression were engineered to expressed human LOX-1-FLAG construct. Isolated clonal lines for each cell type was checked using RT-PCR, immunoblotting and immunofluorescence microscopy. After overnight incubation with tetracycline (1 microgram/ml), cells were starved and incubated with=1, 1'-Dioctadecyl-3, 3, 3', 3'-Tetramethylindocarbocyanine Perchlorate (DiI)-labelled oxLDL (10 microgram/ml) for 30 min. Cells were fixed and imaged to characterise the uptake of OxLDL. Blocking experiments using 5 different affimers, was carried out by adding affimer prior to incubation with DiI-oxLDL. Effects on oxLDL binding and cellular accumulation was evaluated using fluorescence microscopy. Results: The levels of LOX-1-FLAG mRNA were significantly raised (p<0.001) in both cell types in response to tetracycline. Porcine endothelial cells also had significant levels of endogenous native porcine LOX-1(Figure 1). The presence of human LOX-1-FLAG protein was confirmed by immunofluorescence microscopy (Figure 2a). Incubation with oxLDL demonstrated tetracycline-dependent labelled lipid particle uptake in HEK293T LOX-1-FLAG expressing cells. In contrast, oxLDL uptake was not significantly raised compared to uninduced baseline in PAEC LOX-1-FLAG expressing cells. Incubation with LOX-1 binding affimers led to a decrease in oxLDL uptake in both cell lines after induction of LOX-1-FLAG expression (Figure 2b). Conclusion: We have successfully constructed two mammalian cell lines with a stable, inducible LOX-1 expression system. This has allowed us to demonstrate LOX-1-dependent oxLDL uptake. However, such expression is dependent on negligible expression of other scavenger receptors that mediate oxLDL binding and/or uptake. The use of LOX-1-specific affimers show that oxLDL binding and/or uptake is significantly decreased in both cell lines. Future experiments aim to determine the effects of such LOX-1-specific affimers in primary vascular cells and animal models in the context of atherosclerosis and vascular disease.